Application comparison of paediatric myocardial protection procedures in arterial switch surgery - Münch, Frank; Kohl, Matthias; Kwapil, Nicola; Dewald, Oliver; Cuomo, Michela; Purbojo, Ariawan (Perfusion-Uk, 2024)
Background: Reliable myocardial protection is essential for a good outcome after arterial switch operation. Patients and Methods: We evaluated 56 neonates with arterial switch operation in this retrospective study. Three types of cardioplegia were used: antegrade Custodiol® (CCC) n = 22, antegrade Custodiol® plus paediatric microplegia (mix) n = 14, and antegrade plus retrograde intermittently paediatric microplegia (blood) n = 20. We evaluated the extent of myocardial injury using troponin I, Creatine kinase (CK), CK-MB (CK in myocardial cells) and vasoactive inotrope score (VIS), immediately- and the first postoperative day, as well as outcome parameters. A statistical analysis was conducted using multiple linear regression, with adjustments made for the RACHS score and ischemia time, at a significance level of 5%. Results: Preoperative data were comparable between the three groups. Aortic cross clamp time was significantly different between the three groups (CCC: 115 ± 26 min: mix: 162 ± 35 min: blood: 153 ± 31 min). We found significantly lower troponin I release in the blood group 14 ng/mL [CI95 10; 18] versus CCC group 36 ng/mL [CI95 27; 48] and versus mix group 27 ng/mL [CI95 19; 38]; troponin I 24 h blood group 8 ng/mL [CI95 6; 11] versus CCC group 14 ng/mL [CI95 10; 19]. No significant differences were found in CK, CK-MB, VIS, as well as in outcome parameters 30-day mortality, ventilation time, hospital stay or ECMO implantation. Conclusions: Intermittent paediatric microplegia led to a significantly lower release of troponin I, despite significantly longer ischemia times than after application of Custodiol®. Paediatric microplegia can be safely performed in neonates and also offers the advantage of miniaturization of the Cardiopulmonary bypass setup.
CRIS-Team Scopus Importer:2025-02-04
Keywords: arterial switch operation; cardioplegia; cardiopulmonary bypass (CPB); microplegia; myocardial protection; paediatric

Assessing viability of extracorporeal preserved muscle transplants using external field stimulation: a novel tool to improve methods prolonging bridge-to-transplantation time. - Taeger, Christian; Friedrich, Oliver; Dragu, Adrian; Weigand, Annika; Hobe, Frieder; Drechsler, Caroline; Geppert, Carol-Immanuel; Arkudas, Andreas; Münch, Frank; Buchholz, Rainer; Pollmann, Charlotte; Schramm, Axel; et al. (Scientific Reports, 2015)
Preventing ischemia-related cell damage is a priority when preserving tissue for transplantation. Perfusion protocols have been established for a variety of applications and proven to be superior to procedures used in clinical routine. Extracorporeal perfusion of muscle tissue though cumbersome is highly desirable since it is highly susceptible to ischemia-related damage. To show the efficacy of different perfusion protocols external field stimulation can be used to immediately visualize improvement or deterioration of the tissue during active and running perfusion protocols. This method has been used to show the superiority of extracorporeal perfusion using porcine rectus abdominis muscles perfused with heparinized saline solution. Perfused muscles showed statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. The combination of extracorporeal perfusion and external field stimulation may improve organ conservation research.

Assessment of the plasticizer exposure of hospital workers regularly handling medical devices: A pilot study - Eckert, Elisabeth; Kuhlmann, Laura; Göen, Thomas; Münch, Frank (Environmental Research, 2023)
Plastic medical devices, e.g. infusion sets, blood bags or tubing material, that are used manifold in the medical treatment of hospital patients, usually contain considerable amounts of plasticizers. Whereas several studies showed highly elevated inner plasticizer levels of patients treated with plasticized medical devices, little is known about the exposure situation of hospital staff. The present pilot study aimed to evaluate the urinary plasticizer metabolite levels of selected hospital workers of the blood bank (medical technical assistants, MTA) and of perfusionists that are regularly handling plasticized medical devices in order to estimate the work-related amount of the inner individual plasticizer exposure. The study subjects were asked to collect pre- and post-shift spot urine samples over the course of a working week, that were subsequently analyzed for selected urinary metabolites of the plasticizers DEHP, DINCH, DEHTP and TEHTM. Although the observed differences were rather low, a differentiated approach revealed a perceptible impact of the respective workplace environment on the individual urinary plasticizer metabolite levels. Thus, the group of blood bank MTA showed significantly elevated increment levels of urinary DEHP and DINCH metabolites, while the group of perfusionists, showed a considerable higher detection frequency of the main urinary TEHTM metabolite. All in all, however, it can be cautiously concluded by the results of the presented pilot study that a regular handling of plasticized medical devices by hospital employees (via inhalation or dermal contact) contributes demonstrably but yet only marginally to the individual internal plasticizer exposure.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Alternative plasticizers; Biomonitoring; Human study; Occupational exposure; Phthalate; Urine

Comparable Cerebral Blood Flow in Both Hemispheres During Regional Cerebral Perfusion in Infant Aortic Arch Surgery - Rueffer, Andre; Tischer, Philip; Münch, Frank; Purbojo, Ariawan; Toka, Okan; Rascher, Wolfgang; Cesnjevar, Robert; Juengert, Joerg (Annals of Thoracic Surgery, 2017)
Cerebral protection during aortic arch repair can be provided by regional cerebral perfusion (RCP) through the innominate artery. This study addresses the question of an adequate bilateral blood flow in both hemispheres during RCP.Fourteen infants (median age 11 days [range, 3 to 108]; median weight, 3.6 kg [range, 2.8 to 6.0 kg]) undergoing RCP (flow rate 54 to 60 mL · kg(-1) · min(-1)) were prospectively included. Using combined transfontanellar/transtemporal two- and three-dimensional power/color Doppler sonography, cerebral blood flow intensity in the main cerebral vessels was displayed. Mean time average velocities were measured with combined pulse-wave Doppler in the basilar artery, and both sides of the internal carotid, anterior, and medial cerebral arteries. In addition, bifrontal regional cerebral oximetry (rSO2) was assessed. Comparing both hemispheres, measurements were performed at target temperature (28°C) during full-flow total body perfusion (TBP) and RCP.A regular circle of Willis with near-symmetric blood flow intensity to both hemispheres was visualized in all infants during both RCP and TBP. In the left internal carotid artery, blood flow direction was mixed (retrograde, n = 5; antegrade, n = 8) during TBP and retrograde during RCP. Comparison between sides showed comparable cerebral time average velocities and rSO2, except for higher time average velocities in the right internal carotid artery (TBP p = 0.019, RCP p = 0.09). Unilateral comparison between perfusion methods revealed significantly higher rSO2 in the right hemisphere during TBP (82% ± 9%) compared with RCP (74% ± 11%, p = 0.036).Bilateral assessment of cerebral rSO2 and time average velocity in the main great cerebral vessels suggests that RCP is associated with near-symmetric blood flow intensity to both hemispheres. Further neurodevelopmental studies are necessary to verify RCP for neuroprotection during aortic arch repair.
EVALuna2:25812

Comparative study on the migration of di-2-ethylhexyl phthalate (DEHP) and tri-2-ethylhexyl trimellitate (TOTM) into blood from PVC tubing material of a heart-lung machine - Eckert, Elisabeth; Münch, Frank; Göen, Thomas; Purbojo, Ariawan; Mueller, Johannes; Cesnjevar, Robert (Chemosphere, 2016)
Medical devices like blood tubing often consist of PVC material that requires the addition of plasticizers. These plasticizers may migrate into the blood leading to an exposure of the patients. In this study the migration behavior of three different blood tubing sets (PVC material with two different plasticizers and silicone as control material) applied on a heart-lung machine standardly used for cardiopulmonary bypass (CPB) in children was studied. We analyzed the total plasticizer migration by analysis of both, the parent compounds as well as their primary degradation products in blood. Additionally, the total mass loss of the tubing over perfusion time was examined. The PVC tubing plasticized with DEHP (di-2-ethylhexyl phthalate) was found to have the highest mass loss over time and showed a high plasticizer migration rate. In comparison, the migration of TOTM (tri-2-ethylhexyl trimellitate) and its primary degradation products was found to be distinctly lower (by a factor of approx. 350). Moreover, it was observed that the storage time of the tubing affects the plasticizer migration rates. In conclusion, the DEHP substitute TOTM promises to be an effective alternative plasticizer for PVC medical devices particularly regarding the decreased migration rate during medical procedures.
EVALuna2:9736

Deep hypothermic circulatory arrest or tepid regional cerebral perfusion: impact on haemodynamics and myocardial integrity in a randomized experimental trial - Kellermann, Stephanie; Janssen, Carina; Münch, Frank; Koch, Anna Maria; Schneider-Stock, Regine; Cesnjevar, Robert; Rueffer, Andre (Interactive Cardiovascular and Thoracic Surgery, 2017)
OBJECTIVES: Organ protective management during aortic arch surgery comprises deep hypothermic (18°C) circulatory arrest (DHCA), or moderate hypothermia (28°C/ 'tepid') with regional cerebral perfusion (TRCP). The aim of this experimental study was to evaluate the effect of distinct organ protective management on hemodynamic performance and myocardial integrity. METHODS: Ten male piglets were randomized to group DHCA (n = 5) or TRCP (n = 5) group and operated on cardiopulmonary bypass (CPB) with 60 min of aortic cross-clamping. Blood gas analysis was performed throughout the experiment. Haemodynamic assessment was performed using a thermodilution technique before and after CPB. Myocardial biopsies were taken 2 h after CPB and evaluated using terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-biotin nick-end labelling assay and western blot analysis. RESULTS: At reperfusion, levels of central venous saturation were significantly higher (P = 0.016) and levels of lactate significantly lower (P = 0.029) in the DHCA group. After CPB, thermodilution measurements revealed higher stroke volume and lower peripheral resistance in the TRCP group (P = 0.012 and 0.037). At the end of the experiment, no significant differences regarding laboratory and haemodynamic parameters were evident. All specimens showed enrichment of terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-biotin nick-end labelling-positive cells exclusively at the left ventricular subendocardium with no difference between groups and equal concentrations of cyclo-oxygenase-2. CONCLUSIONS: TRCP is associated with decreased peripheral resistance and higher stroke volume immediately after CPB. However, this beneficial effect is contrasted by signs of lower body hypoperfusion, which is expressed by lower central venous saturations and higher lactate levels. Distinct strategies of organ protection did not seem to affect apoptotic/necrotic and inflammatory changes in the left ventricular myocardium.
EVALuna2:33490

Effect of phospholipid coating on the migration of plasticizers from PVC tubes - Münch, Frank; Höllerer, Christine; Klapproth, Andre; Eckert, Elisabeth; Rueffer, Andre; Cesnjevar, Robert; Göen, Thomas (Chemosphere, 2018)
Plasticizers in polyvinyl chloride (PVC) are not covalently bound to the polymer and can thus migrate into the contact medium. The presented study investigated the potential effects of phospholipid-lining as anti-coagulation coating (ACC) on the migration rate of plasticizers from PVC tubing into blood. For the in-vitro study, five different groups of tubing sets in six replicates were perfused with sheep blood (Group A: PVC plasticized with di-(2-ethylhexyl) phthalate (DEHP) without ACC, Group B: DEHP-plasticized PVC with ACC, Group C: PVC plasticized with tri-(2-ethylhexyl) trimellitate (TOTM) without ACC, Group D: TOTM-plasticized PVC with ACC, Group E (control group): polyolefin material with ACC but without plasticizers). Both the levels of the unchanged plasticizers in blood and the concentration levels of their primary degradation products were assessed. For DEHP, the primary metabolite MEHP (mono-(2-ethylhexyl) phthalate) was determined. The isomers of MEHTM (mono-(2-ethylhexyl) trimellitate) and DEHTM (di-(2-ethylhexyl) trimellitate), respectively, were investigated as primary metabolites of TOTM. The calculated DEHP equivalents (sum of determined levels of DEHP and MEHP) after 24 h of perfusion displayed a tendency towards lower levels in the tubing sets without ACC (Group A (201 ± 56.4 μmol/L)) compared to the tubing sets with ACC (Group B (253 ± 369 μmol/L)). Significantly different DEHP equivalents between Group A and Group B were found after a perfusion time of 6 h and 10 h, respectively. A similar effect was observed for the TOTM-containing tubing sets. However, the absolute plasticizer migration rate of TOTM (TOTM equivalents) after 24 h of perfusion was found to be significantly lower compared to that of DEHP (with a factor of over 200). The results indicate that phospholipid coating (ACC) rather enhances the migration of plasticizers and of their primary degradation products from PVC tubing into streaming blood. The enhancement effect was found to be slightly greater for TOTM, but as TOTM migrates in significantly lower levels than DEHP in all experimental settings, TOTM is confirmed to be a recommendable alternative plasticizer to DEHP in medical devices.
EVALuna2:34678

Equal cerebral perfusion during extended aortic coarctation repair - Rüffer, André; Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Wölfle, Joachim; Jüngert, Jörg M. (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Aortic coarctation with distal aortic arch hypoplasia can be effectively addressed by coarctation resection with extended end-to-end-anastomosis (REEEA). Particularly, when unilateral cerebral perfusion (UCP) is established by clamping of left-sided supra-aortic vessels, the extent of cerebral blood flow distribution during repair remains undetermined, so far. Transfontanellar contrast-enhanced ultrasound (T-CEUS) can be utilized for real-time visualization and quantitative evaluation of cerebral blood flow. This study quantitatively evaluates cerebral perfusion during REEEA by using intraoperative T-CEUS. METHODS: In a prospective study, 9 infants with open fontanelle undergoing REEEA [median age: 13 days (range 1-34) and median weight 3.1 kg (range 2.2-4.4)] were intraoperatively examined with T-CEUS at 3 consecutive time-points: before skin incision, during UCP and after skin suture. A software-based analysis of 11 parameters was used for data evaluation. Absolute and relative blood flow in contralateral hemispheres was measured in side-by-side comparison, and referenced to baseline measurements. RESULTS: No side-depend absolute or relative cerebral perfusion differences were found during REEEA, except for an increased relative 'wash-out-rate' (P = 0.0013) in favour of the right hemisphere after surgery. Compared to ipsilateral baseline levels, 'rise time' was transiently increased in right (P = 0.0277) and 'time-to-peak' in both hemispheres (right: P = 0.0403 and left: P = 0.0286), all during UCP. CONCLUSIONS: The use of T-CEUS provided evidence for homogenous distribution of contrast agent in both hemispheres during UCP. T-CEUS can be utilized for the postprocedural evaluation of cerebral perfusion during congenital cardiac surgery. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov Unique, Identifier: NCT03215628.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Aortic coarctation; Cerebral perfusion; Extended end-to-end-anastomosis

Extracorporeal perfusion - reduced to a one-way infusion. - Taeger, Christian Dirk; Friedrich, Oliver; Horch, Raymund E.; Drechsler, Caroline; Weigand, Annika; Hopf, Fabio; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Wenzel, Carina; Geis, Sebastian; Prantl, Lukas; et al. (Clinical hemorheology and microcirculation, 2017)
BACKGROUND Extracorporeal perfusion (EP) is moving into focus of research in reconstructive and transplantation medicine for the preservation of amputates and free tissue transplants. The idea behind EP is the reduction of ischemia-related cell damage between separation from blood circulation and reanastomosis of the transplant. Most experimental approaches are based on a complex system that moves the perfusate in a circular course. OBJECTIVE AND METHODS In this study, we aimed to evaluate if a simple perfusion by an infusion bag filled with an electrolyte solution can provide acceptable results in terms of flow stability, oxygen supply and viability conservation for EP of a muscle transplant. The results are compared to muscles perfused with a pump system as well as muscles stored under ischemic conditions with a one-time intravasal flushing with Jonosteril. RESULTS With this simple method a sufficient oxygen supply could be achieved and functionality could be maintained between 3.35 times and 4.60 times longer compared to the control group. Annexin V positive nuclei, indicating apoptosis, increased by 9.7% in the perfused group compared to 24.4% in the control group. CONCLUSIONS Overall, by decreasing the complexity of the system, EP by one-way infusion can become more feasible in clinical situation

Goal-directed-perfusion in neonatal aortic arch surgery - Cesnjevar, Robert; Purbojo, Ariawan; Münch, Frank; Juengert, Joerg; Rueffer, Andre (Translational Pediatrics, 2016)
Reduction of mortality and morbidity in congenital cardiac surgery has always been and remains a major target for the complete team involved. As operative techniques are more and more standardized and refined, surgical risk and associated complication rates have constantly been reduced to an acceptable level but are both still present. Aortic arch surgery in neonates seems to be of particular interest, because perfusion techniques differ widely among institutions and an ideal form of a so called "total body perfusion (TBP)" is somewhat difficult to achieve. Thus concepts of deep hypothermic circulatory arrest (DHCA), regional cerebral perfusion (RCP/with cardioplegic cardiac arrest or on the perfused beating heart) and TBP exist in parallel and all carry an individual risk for organ damage related to perfusion management, chosen core temperature and time on bypass. Patient safety relies more and more on adequate end organ perfusion on cardiopulmonary bypass, especially sensitive organs like the brain, heart, kidney, liver and the gut, whereby on adequate tissue protection, temperature management and oxygen delivery should be visualized and monitored.
EVALuna2:34094

How to administer near-infrared spectroscopy in critically ill neonates, infants, and children - Bruns, Nora; Moosmann, Julia; Münch, Frank; Dohna-Schwake, Christian; Wölfle, Joachim; Cesnjevar, Robert; Dittrich, Sven; Felderhoff-Müser, Ursula; Müller, Hanna (Journal of Visualized Experiments, 2020)
Near infrared spectroscopy (NIRS) calculates regional tissue oxygenation (rSO2) using the different absorption spectra of oxygenated and deoxygenated hemoglobin molecules. A probe placed on the skin emits light that is absorbed, scattered, and reflected by the underlying tissue. Detectors in the probe sense the amount of reflected light: this reflects the organ-specific ratio of oxygen supply and consumption-independent of pulsatile flow. Modern devices enable the simultaneous monitoring at different body sites. A rise or dip in the rSO2 curve visualizes changes in oxygen supply or demand before vital signs indicate them. The evolution of rSO2 values in relation to the starting point is more important for interpretation than are absolute values. A routine clinical application of NIRS is the surveillance of somatic and cerebral oxygenation during and after cardiac surgery. It is also administered in preterm infants at risk for necrotizing enterocolitis, newborns with hypoxic ischemic encephalopathy and a potential risk of impaired tissue oxygenation. In the future, NIRS could be increasingly used in multimodal neuromonitoring, or applied to monitor patients with other conditions (e.g., after resuscitation or traumatic brain injury).
CRIS-Team Scopus Importer:2020-09-18

Hydroxyethyl starch solution for extracorporeal tissue perfusion - Taeger, Christian; Friedrich, Oliver; Drechsler, Caroline; Weigand, Annika; Hobe, Frieder; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Buchholz, Rainer; Horch, Raymund E.; Präbst, Konstantin; Buchholz, Rainer (Clinical hemorheology and microcirculation, 2016)
In the field of free flap transfer in reconstructive surgery, the trans- or replanted tissue always undergoes cell damage during ischemia to a more or less strong extent. In previous studies we already showed that conserving muscle transplants by means of extracorporeal perfusion over a period of 6 hours by using a crystalloid solution for perfusion. However, we observed significant edema formation. In this study we aimed at reducing the edema formation by using an iso-oncotic colloid as perfusion solution. This way we want to evaluate a possible new application of hydroxyl-ethyl starch in an extracorporeal setup to exploit potential benefits of the colloid.Examined parameters include the muscles' functionality with external field stimulation, histological examination and edema formation. Perfused muscles showed a statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. Substituting the electrolyte perfusion solution with a colloidal one shows the tendency to reduce the edema formation but without statistical significance.

Improved contractility with tepid modified full blood cardioplegia compared with cold crystalloid cardioplegia in a piglet model - Münch, Frank; Purbojo, Ariawan; Kellermann, Stephanie; Janssen, Carina; Cesnjevar, Robert; Rueffer, Andre (European Journal of Cardio-Thoracic Surgery, 2015)
Experience regarding warm blood cardioplegia according to Calafiore results from its broad use in adult patients. In this experimental study, tepid (28°C) modified full blood cardioplegia (MBC) was adopted for paediatric use and compared with cold crystalloid cardioplegia (CCC).Twenty male piglets (mean weight: 11.1 ± 1.0 kg) were operated on cardiopulmonary bypass (CPB) in moderate hypothermia (28°C) and randomized to MBC (n = 8) or CCC (n = 12) for 60 min aortic cross-clamping. Blood levels of myocardial proteins [N-terminal pro-brain natriuretic peptide (NT-pro-BNP), myoglobin, creatine kinase type MB and troponin-I] were investigated at the beginning of the experiment and after CPB. Haemodynamic measurements included thermodilution and conductance-catheter technique inserted through the left ventricle-apex. Pressure-volume loop analysis was performed with dobutamine-stress test and inflow occlusion, enabling preload independent evaluation of myocardial performance. Changes of measured data post-CPB were calculated in relation to baseline-levels (%).Baseline and operative data in both groups were similar. During the experiment, cardiac markers showed no significant variations between groups. Pressure-volume loop analysis during stress test revealed a significantly higher preload independent contractility (slope of end-systolic pressure-volume relation: Ees) with MBC compared with CCC (MBC: 123 ± 35% [confidence interval (CI95): 93-153] vs CCC: 78 ± 34% [CI95: 54-102]; P = 0.042), whereas cardiac output was not significantly different between groups MBC: 122 ± 16% [95% confidence interval (CI95): 109-135] vs CCC: 105 ± 17% [CI95: 93-116]; P = 0.069.This randomized animal study proves feasibility and safety of MBC for paediatric use. Haemodynamic evaluation and cardiac markers did not show inferiority to standard CCC. Moreover, MBC seems to be associated with superior contractility post bypass, which encourages us to use MBC in paediatric patients in the near future.
EVALuna2:25808

Influence of factor XIII activity on post-operative transfusion in congenital cardiac surgery-A retrospective analysis - Fahlbusch, Fabian B.; Heinlein, Thomas; Rauh, Manfred; Dittrich, Sven; Cesnjevar, Robert; Moosmann, Julia; Nadal, Jennifer; Schmid, Matthias; Münch, Frank; Schroth, Michael; Rascher, Wolfgang; Topf, Hans-Georg (PLoS ONE, 2018)
OBJECTIVES: Coagulation factor XIII (FXIII) plays a key role in fibrin clot stabilization-an essential process for wound healing following cardiothoracic surgery. However, FXIII deficiency as a risk for post-operative bleeding in pediatric cardiac surgery involving cardiopulmonary bypass (CPB) for congenital heart disease (CHD) is controversially discussed. Thus, as primary outcome measures, we analyzed the association of pre-operative FXIII activity and post-operative chest tube drainage (CTD) loss with transfusion requirements post-operatively. Secondary outcomes included the influence of cyanosis and sex on transfusion. METHODS: Our retrospective analysis (2009-2010) encompassed a single center series of 76 cardio-surgical cases with CPB (0-17 years, mean age 5.61 years) that were post-operatively admitted to our pediatric intensive care unit (PICU). The observational period was 48 hours after cardiac surgery. Blood cell counts and coagulation status, including FXIII activity were routinely performed pre- and post-operatively. The administered amount of blood products and volume expanders was recorded electronically, along with the amount of CTD loss. Uni- and multivariate logistic regression analysis was performed to calculate the associations (odds ratios) of variables with post-operative transfusion needs. RESULTS: FXIII activities remained stable following CPB surgery. There was no association of pre- and post-operative FXIII activities and transfusion of blood products or volume expanders in the first 48 hours after surgery. Similarly, FXIII showed no association with CTD loss. Cyanosis and female sex were associated with transfusion rates. CONCLUSIONS: Although essentially involved in wound healing and clotting after surgery, FXIII activity does not serve as a valid predictor of post-operative transfusion need.
EVALuna2:35481

Ischaemia-related cell damage in extracorporeal preserved tissue - new findings with a novel perfusion model - Taeger, Christian; Müller-Seubert, Wibke; Horch, Raymund E.; Präbst, Konstantin; Münch, Frank; Geppert, Carol-Immanuel; Birkholz, Torsten; Dragu, Adrian (Journal of Cellular and Molecular Medicine, 2014)
Tissue undergoing free transfer in transplant or reconstructive surgery always is at high risk of ischaemia-related cell damage. This study aims at assessing different procedures using an extracorporeal perfusion and oxygenation system to investigate the expression of hypoxia inducible factor (HIF)-1-? as marker for hypoxia and of the pro-apoptotic protein Caspase-3 in skeletal muscle to elucidate potential improvements in tissue conservation. Twenty-four porcine rectus abdominis muscles were assigned to five different groups and examined after they had been extracorporeally preserved for 60 min. time. Group I was left untreated (control), group II was perfused with a cardioplegic solution, group III was flushed with 10 ml of a cardioplegic solution and then left untreated. Group IV and V were perfused and oxygenated with either an isotone crystalloid solution or a cardioplegic solution. Among others, immunohistochemistry (Caspase-3 and HIF-1-?) of muscle samples was performed. Furthermore, oxygen partial pressure in the perfusate at the arterial and venous branch was measured. Expression of Caspase-3 after 60 min. was reduced in all groups compared to the control group. Furthermore, all groups (except group III) expressed less HIF-1-? than the control group. Oxygenation leads to higher oxygen levels at the venous branch compared to groups without oxygenation. Using an extracorporeal perfusion and oxygenation system cell damage could be reduced as indicated by stabilized expressions of Caspase-3 and HIF-1-? for 60 min. of tissue preservation. Complete depletion of oxygen at the venous branch can be prevented by oxygenation of the perfusate with ambient air.
EVALuna2:6573

Kompetenzen von Perfusionist:innen und Ausbildungsstrukturen in der Perfusiologie - Münch, Frank (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Perfusionists are members of an interdisciplinary and multiprofessional team that enables and improves the complex treatment of patients by combining expertise in cardiac surgery, anesthesiology, cardiology, pulmonology, healthcare and nursing. The expertise is particularly focused on the utilization of extracorporeal circulation (ECC). Given the absence of a training program for perfusionists in the Federal Republic of Germany, the German Society for Cardiovascular Engineering (DGfK) as the responsible professional society, has recognized and recommended the contents of the European Certificate in Cardiovascular Perfusion (ECCP) as a basic qualification or minimum standard for perfusionists in Germany as early as 2010. In addition to the classical ECC-related requirements the professional field is increasingly being broadened by collaboration in the development of innovative medical products. These new requirements and necessary competences must be taken into account in the study curricula of perfusion science to adequately prepare the profession for the future. It is recommended that practice-oriented degree programs in technical medicine, medical technology and biomedical engineering with a focus on perfusion science or clinical perfusion should include a minimum of 60 European credit transfer system (ECTS) points in the field of perfusion science. Future employers must have confidence that all graduates possess the same fundamental competencies with respect to perfusion. This requirement can only be fulfilled by an adapted study content. In this respect the Academic Advisory Board of the DGfK published a position paper entitled “Competences perfusion science and technical medicine 2030” in 2024, which sets out the future requirements for the profession.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Cardiology; Consensus; ECCP; Qualifications; Standards

Microplegia in paediatric hearts - Münch, Frank; Kwapil, Nicola; Teske, Andreas; Rueffer, Andre; Dittrich, Sven; Volk, Tilmann; Purbojo, Ariawan (Perfusion-Uk, 2022)
Introduction A basic prerequisite for a good surgical outcome in heart surgery is optimal myocardial protection. However, cardioplegia strategies used in adult cardiac surgery are not directly transferable to infant hearts. Paediatric microplegia, analogous to Calafiore cardioplegia used in adult cardiac surgery, offers the advantage of safe myocardial protection without haemodilution. The use of concentration-dependent paediatric microplegia is new in clinical implementation. Material and methods Paediatric microplegia has been in clinical use in our institution since late 2014. It is applied via an 1/8 inch tube of a S5-HLM roller pump (LivaNova, Italy). As cardioplegic additive, a mixture of potassium (K) 20 mL (2 mmol/mL potassium chloride 14.9% Braun) and magnesium (Mg) 10 mL (4 mmol/mL Mg-sulphate Verla (R) i. v. 50%) is fixed into a syringe-pump (B. Braun, Germany). This additive is mixed with arterial patient blood from the oxygenator in different flow dependent ratios to form an effective cardioplegia. Technique After microplegia application of initially 25 mmol/L K with 11 mmol/L Mg for 2 min, a safe cardioplegic cardiac arrest is achieved, which after release of the coronary circulation, immediately returns to a spontaneous cardiac-rhythm. In the case of prolonged aortic clamping, microplegia is repeated every 20 min with a reduction of the application dose of K by 20% and Mg by 30% (20 mmol/L K; 8.5 mmol/L Mg) and a further reduction down to a maintenance dose (15 mmol/L K; 6 mmol/L Mg) after additional 20 min. The microplegia adapted to the needs of paediatric myocardium is convincing due to its simple technical implementation for the perfusionist while avoiding haemodilution. However, the required intraoperative interval of microplegia of approx. 20 min demands adapted intraoperative management from the surgeon.
CRIS-Team WoS Importer:2022-09-30

Migration von Weichmachern und Beschichtungen während der extrakorporalen Perfusion in der Kardiotechnik - Münch, Frank; Göen, Thomas; Schulbert, Christian; Cesnjevar, Robert; Ihlenburg, Katharina Susanne (Abstracts der 40. Internationalen Jahrestagung der DGfK und 3. Fokustagung Herz, 2011)
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IGM.LP.migrat

Minimized Hemodiafiltration for Extracorporeal Membrane Oxygenation in Infants - Kwapil, Nicola; Teske, Andreas; Dittrich, Sven; Blumauer, Robert; Cuomo, Michela; Purbojo, Ariawan; Münch, Frank (Thoracic and Cardiovascular Surgeon, 2023)
BACKGROUND: Fluid overload is a serious complication in the treatment of infants with extracorporeal membrane oxygenation (ECMO). Volume overload leads to prolonged ECMO therapy if left untreated. The renal replacement therapy of choice in pediatric patients is peritoneal dialysis or conventional dialysis using a "large" hemofiltration machine via a Shaldon catheter or directly connected to the ECMO system. This study describes the implementation of a novel minimized hemodiafiltration (HDF) system in pediatric patients on ECMO. METHODS: This retrospective analysis included 13 infants up to 5 kg who underwent 15 veno-arterial (V-A) ECMO runs with HDF. A minimized HDF system is integrated into an existing ECMO system (18-mL priming volume), connected post-oxygenation to the venous line, before the ECMO pump. Two infusion pumps are attached to the inlet and outlet of the hemofilter to control the HDF system.In addition to retention values (creatine and urea) at six defined time points, flow rates, dialysis parameters, and volume withdrawal were examined, as well as the number of HDF system changes. RESULTS: With a mean ECMO runtime of 156 hours, the HDF system was utilized for 131 hours. The mean blood flow through the hemofilter was 192 mL/min. The mean dialysate flow was 170 mL/h, with a mean volume deprivation of 39 mL/h. The HDF system was changed once in seven cases and twice in three cases. CONCLUSION: There were no complications with the minimized HDF system in all 15 applications. It allows safe patient volume management when treating infants with ECMO, with effective elimination of urinary substances.
CRIS-Team Scopus Importer:2023-04-21

Mobility and freedom of movement: A novel out-of-hospital treatment for pediatric patients with terminal cardiac insufficiency and a ventricular assist device - Rottermann, Kathrin; Dittrich, Sven; Dewald, Oliver; Teske, Andreas; Kwapil, Nicola; Bleck, Steffen; Purbojo, Ariawan; Münch, Frank (Frontiers in Cardiovascular Medicine, 2022)
Background: Due to rapid medical and technological progress, more and more pediatric patients with terminal cardiac insufficiency are being implanted with a ventricular assist device as a bridge to transplant without legal approval for hospital discharge. EXCOR (R) Active is a recently developed mobile driving unit for the EXCOR (R) ventricular assist device (EXCOR (R) VAD) with a long-lasting battery life that can manage small blood pumps, offering improved mobility for pediatric patients. This study strives to elaborate the requirements necessary for a safe home healthcare environment (HHE) for pediatric patients on EXCOR (R) VAD powered by the EXCOR (R) Active driving unit. Materials and methods: Patient- and device-related preconditions (medical, ethical, psychological, technical, structural, organizational) were analyzed with regard to feasibility and safety in three individual patient cases. Included were pediatric patients with terminal cardiac insufficiency in a stable medical condition receiving in-hospital treatment with a univentricular or biventricular EXCOR (R) VAD powered by EXCOR (R) Active. Analysis was single-center, data was obtained 05/2020-02/2022. Results: A total of three patients on EXCOR (R) VAD were identified for HHE treatment with the EXCOR (R) Active driving unit. Switch was performed safely and increased mobility led to improved psychomotor development and improved quality of life. No complications directly related to HHE-treatment occurred. One patient recently underwent an orthotopic heart transplant, one patient remains in HHE, and one patient died due to a complication not related to the HHE. Ethical approval for off-label use was obtained and patients and parents were given the required technical training and psychological support. Caregivers and medical professionals involved in the patients' care at home were briefed intensely. Remote consultations were implemented and interdisciplinary in-hospital checks reduced to a long-term 4-week-scheme. Conclusion: While it is challenging to discharge pediatric patients being treated with a paracorporeal ventricular assist device (EXCOR (R) VAD) from hospital, it is feasible and can be managed safely with the novel driving unit EXCOR (R) Active. A HHE may help to improve patients' psychomotor development, offer normalized social contacts and strengthen both patients' and parents' physical and mental resources. Legal approval and another study with a larger sample size are warranted.
CRIS-Team WoS Importer:2022-12-30

Multisite measurement of regional oxygen saturation in Fontan patients with and without protein-losing enteropathy at rest and during exercise - Schroeer, Simon; Fahlbusch, Fabian B.; Münch, Frank; Alkassar, Muhannad; Toka, Hakan R.; Rauh, Manfred; Rueffer, Andre; Cesnjevar, Robert; Dittrich, Sven; Toka, Okan; Moosmann, Julia (Pediatric Research, 2019)
Background: Protein-losing enteropathy (PLE) is a severe complication of Fontan circulation with increased risk of end-organ dysfunction. We evaluated tissue oxygenation via near-infrared spectroscopy (NIRS) at different exercise levels in Fontan patients. Methods: Assessment of multisite NIRS during cycle ergometer exercise and daily activities in three groups: Fontan patients with PLE; without PLE; patients with dextro-transposition of the great arteries (d-TGA); comparing univentricular with biventricular circulation and Fontan with/without PLE. Renal threshold analysis (<65%;<55%;<45%) of regional oxygen saturation (rSO2) was performed. Results: Fontan patients showed reduced rSO2 (p < 0.05) in their quadriceps femoris muscle compared with biventricular d-TGA patients at all time points. rSO2 in renal tissue was reduced at baseline (p = 0.002), exercise (p = 0.0062), and daily activities (p = 0.03) in Fontan patients with PLE. Renal threshold analysis identified critically low renal rSO2 (rSO2 < 65%) in Fontan patients with PLE during exercise (95% of monitoring time below threshold) and daily activities (83.7% time below threshold). Conclusion: Fontan circulation is associated with decreased rSO2 values in skeletal muscle and hypoxemia of renal tissue solely in patients with PLE. Reduced rSO2 already during activities of daily life, might contribute to comorbidities in patients with Fontan circulation, including PLE and renal failure.
CRIS-Team Scopus Importer:2019-05-21

Myocardial Protection During Aortic Arch Repair in a Piglet Model: Beating Heart Technique Compared With Crystalloid Cardioplegia - Janssen, Carina; Kellermann, Stephanie; Münch, Frank; Purbojo, Ariawan; Cesnjevar, Robert; Rueffer, Andre (Annals of Thoracic Surgery, 2015)
Selective myocardial perfusion enables repair of congenital aortic arch obstruction without cardiac arrest. This study was inspired by the lack of prospective controlled studies of the beating heart (BH) technique compared with cold crystalloid cardioplegia (CC) regarding effects on myocardial performance, ischemic damage, and serum electrolyte levels.In a prospective study, 20 male piglets weighing 11.1 ± 1.3 kg were operated on using cardiopulmonary bypass (CPB) and underwent 60 minutes of aortic cross-clamping. According to prospective randomization, myocardial protection included either a BH modification with selective myocardial perfusion using an individual roller pump or CC. Hemodynamic performance was evaluated by a conductance catheter technique before and after CPB and calculated in relation to baseline levels. Laboratory analysis included blood levels of troponin T and serum electrolytes.Eighteen piglets entered analysis. There were significantly higher slopes of end-systolic pressure-volume relations (168% ± 92% versus 89% ± 16%; p = 0.046) and preload-recruitable stroke work (PRSW) (139% ± 37% versus 103% ± 31%; p = 0.040) in BH piglets compared with those who underwent CC. Laboratory analysis during reperfusion revealed higher levels of troponin T (1.31 ± 0.28 ng/mL versus 0.49 ± 0.17 ng/mL; p < 0.01) and sodium (131 ± 4 mmol/L versus 120 ± 8 mmol/L; p = 0.003) and lower levels of potassium (4.8 ± 0.4 mmol/L versus 6.4 ± 1.0 mmol/L; p = 0.001) with BH compared with CC, whereas no significant differences were calculated at the end of the experiment.The BH technique is associated with improved contractility compared with standard CC. There is comparable ischemic damage in both groups, with an earlier rise in blood levels of troponin T after BH and more fluctuation of serum electrolytes with CC. Evidence of ischemic changes should dissuade one from using the BH technique imprudently.
EVALuna2:25809

Pediatric Extracorporeal Life Support Using a Third Generation Diagonal Pump - Speth, Marlene; Münch, Frank; Purbojo, Ariawan; Glöckler, Martin; Toka, Okan; Cesnjevar, Robert; Rueffer, Andre (Asaio Journal, 2016)
This study reports a single-centre experience of the Medos Deltastream diagonal-pump (DP3) for extracorporeal cardiac, pulmonary, or combined support in a single-center pediatric cohort. Twenty-seven consecutive patients with 28 runs of the DP3 between January 2013 and June 2014 were included for analysis. Median patient age, weight, and duration of support were 278 days (range: 0 days-14.2 years), 7.2 kg (range: 2.5-39 kg), and 8 days (range: 2-69 days). Midline sternotomy (n = 20, 71.4%) or cervical approaches (n = 8, 28.6%) were used for cannulation. The DP3 was employed for either veno-arterial extracorporeal life support (ECLS, n = 16), veno-venous extracorporeal membrane oxygenation (ECMO, n = 5), or ventricular assist devices (right ventricular assist device [RVAD], n = 1; left ventricular assist device [LVAD], n = 1; and univentricular assist device [UNIVAD], n = 5). Three patients initially supported with ECLS were switched to UNIVAD and one patient with UNIVAD was changed to ECLS. Required flow for neonates (n = 8) ranged between 0.2 and 0.75 L/min. Irreversible pump damage occurred in one patient during deairing after air block. Successful weaning, 30 day and hospital survival were 89.3% (n = 25), 85.7% (n = 24), and 71.4% (n = 20). All patients on UNIVAD, who did not require further extracorporeal respiratory assist, survived. In conclusion, the DP3 can be used for individual patient demands and adapted to their most suitable method of support. Meticulous flow adjustments render this pump highly effective for extracorporeal support particularly in pediatric patients.
EVALuna2:25117

Plasticizer exposure of infants during cardiac surgery - Eckert, Elisabeth; Müller, Johannes; Höllerer, Christine; Purbojo, Ariawan; Cesnjevar, Robert; Göen, Thomas; Münch, Frank (Toxicology Letters, 2020)
In the present study we investigated the internal exposure situation of infant patients to the plasticizers TEHTM (tri-2-ethylhexyl trimellitate) and DEHP (di-2-ethylhexyl phthalate). The study collective included 21 infant patients aged 2–22 months that had to undergo cardiac surgery using cardio pulmonary bypass (CPB). Each patient, but one, received blood products during surgery. A special feature was that the used CPB tubings were exclusively plasticized with the alternative plasticizer TEHTM and were free of the standard plasticizer DEHP, that raises increasing toxicological concern. The blood products were stored in DEHP plasticized blood bags. Blood and urine samples of each infant patient were analysed before and after the surgery for the levels of the plasticizers DEHP and TEHTM and their metabolites. In general, the plasticizers were detected in the post-surgery blood samples only, with TEHTM in low levels (median 18.4 μg/L) and DEHP in rather elevated levels (median 1046 μg/L). With respect to the urine samples, TEHTM metabolites were not detected in any of the samples. DEHP metabolites were found in all urine samples, however, in significantly increased median levels in the post-surgery urine samples of the infants (increase factor 5–26). Thus, the present study clearly demonstrates the strong contribution of standard medical procedures to the internal plasticizer burden of patients. Particularly with regard to the suspected endocrine disrupting activities of the phthalate plasticizer DEHP, the elevated internal levels of this plasticizer and its metabolites in infants following cardiac surgery are alarming.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Biomonitoring; Cardio pulmonary bypass; DEHP; Medical devices; Packed red blood cells; TOTM; Urine

Reduction of exposure to plasticizers in stored red blood cell units - Münch, Frank; Göen, Thomas; Zimmermann, Robert; Adler, Werner; Purbojo, Ariawan; Höllerer, Christine; Cesnjevar, Robert; Rüffer, André (Perfusion-Uk, 2019)
Introduction: Plastic can be toxic and hazardous to an organism’s health, but it is being widely used in our daily lives. Di-2-ethylhexyl-phthalate is the most common plasticizer in medical devices made of polyvinylchloride and is commonly found in soft bags storing red blood cell units. Di-2-ethylhexyl-phthalate and its degradation product mono-2-ethylhexyl-phthalate can migrate into human body fluids, for example, blood and tissues. The aim of the study was to assess the concentration of plasticizers in red blood cell units according to storage time and after mechanical rinsing using a cell salvage device. Methods: Levels of di-2-ethylhexyl-phthalate and mono-2-ethylhexyl-phthalate were analysed in 50 unwashed red blood cell units using liquid chromatography coupled with tandem mass spectrometry. In addition, phthalate concentrations were measured before and after mechanical rinsing in six more washed red blood cell units with storage times ranging between 36 and 56 days. A linear regression model was determined by the daily increase of di-2-ethylhexyl-phthalate and mono-2-ethylhexyl-phthalate in the stored red blood cell units subject to their storage time (range = 4-38 days), and the effect of mechanical rinsing on their phthalate concentration was calculated. Results: A linear correlation was found between storage time of unwashed red blood cell units and the concentration of di-2-ethylhexyl-phthalate (p < 0.001) or mono-2-ethylhexyl-phthalate (p < 0.001). Stored red blood cell units older than 14 days had significantly higher concentrations of both contaminants than red blood cell units of shorter storage time (p < 0.001). Mechanical rinsing in washed red blood cell units attained a reduction in the di-2-ethylhexyl-phthalate and mono-2-ethylhexyl-phthalate concentration by a median of 53% (range = 18-68%; p = 0.031) and 87% (range = 68-96%; p = 0.031), respectively. Conclusion: Leaching of di-2-ethylhexyl-phthalate and mono-2-ethylhexyl-phthalate into red blood cell units depends on the duration of storage time. Plasticizers can be significantly reduced by mechanical rinsing using cell salvage devices, and thus, red blood cell units can be regenerated with respect to chemical contamination.
CRIS-Team Scopus Importer:2019-06-18
Keywords: di-2-ethylhexyl-phthalate; mechanical rinsing; plasticizers; red blood cell units; storage time

Transfontanellar Contrast-Enhanced Ultrasound for Monitoring Brain Perfusion During Neonatal Heart Surgery - Knieling, Ferdinand; Rüffer, André; Cesnjevar, Robert; Regensburger, Adrian; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Meyer, Sebastian; Strobel, Deike; Rascher, Wolfgang; Wölfle, Joachim; et al. (Circulation: Cardiovascular Imaging, 2020)
CRIS-Team Scopus Importer:2020-03-13

Transfontanellar Contrast-enhanced US for Intraoperative Imaging of Cerebral Perfusion during Neonatal Arterial Switch Operation - Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Wagner, Alexandra; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Wölfle, Joachim; Jüngert, Jörg M.; Rüffer, André (Radiology, 2022)
Background Brain injury and subsequent neurodevelopmental disorders are major determinants for later-life outcomes in neonates with transposition of the great arteries (TGA). Purpose To quantitatively assess cerebral perfusion in neonates with TGA undergoing arterial switch operation (ASO) using transfontanellar contrast-enhanced US (T-CEUS). Materials and Methods In a prospective single-center cross-sectional diagnostic study, neonates with TGA scheduled for ASO were recruited from February 2018 to February 2020. Measurements were performed at five time points before, during, and after surgery (T1-T5), and 11 perfusion parameters were derived per cerebral hemisphere. Neonate clinical characteristics, heart rate, mean arterial pressure, central venous pressure, near-infrared spectroscopy, blood gas analyses, ventilation time, time spent in the pediatric intensive care unit, and time in hospital were correlated with imaging parameters. Analysis of variance or a mixed-effects model were used for groupwise comparisons. Results A total of 12 neonates (mean gestational age, 39 6/7 weeks ± 1/7 [SD]) were included and underwent ASO a mean of 6.9 days ± 3.4 after birth. When compared with baseline values, T-CEUS revealed a longer mean time-to-peak (right hemisphere, 4.3 seconds ± 2.1 vs 17 seconds ± 6.4 [P < .001]; left hemisphere, 4.0 seconds ± 2.3 vs 21 seconds ± 8.7 [P < .001]) and rise time (right hemisphere, 3.5 seconds ± 1.7 vs 11 seconds ± 5.1 [P = .002]; left hemisphere, 3.4 seconds ± 2.0 vs 22 seconds ± 7.8 [P = .004]) in both cerebral hemispheres during low-flow cardiopulmonary bypass and hypothermia (T4) for all neonates. Neonate age at surgery negatively correlated with T-CEUS parameters during ASO, as calculated with the area under the flow curve (AUC) during wash-in (R = -0.60, P = .020), washout (R = -0.82, P = .002), and both wash-in and washout (R = -0.79, P = .004). Mean AUC values were lower in neonates older than 7 days compared with younger neonates during wash-in ([87 arbitrary units au ± 77] × 102 vs [270 au ± 164] × 102, P = .049]), washout ([15 au ± 11] × 103 vs [65 au ± 38] × 103, P = .020]) and both wash-in and washout ([24 au ± 18] × 103 vs [92 au ± 53] × 103, P = .023). Conclusion Low-flow hypothermic conditions resulted in reduced cerebral perfusion, as measured with transfontanellar contrast-enhanced US, which inversely correlated with age at surgery. Clinical trial registration no. NCT03215628 © RSNA, 2022 Online supplemental material is available for this article.
CRIS-Team Scopus Importer:2022-07-01

Troponin I levels in extracorporeal membrane oxygenation following congenital heart surgery - Rüffer, André; Münch, Frank; Potapov, Sergej; Purbojo, Ariawan; Toka, Okan; Dodge-Khatami, Ali; Dittrich, Sven; Cesnjevar, Robert (World Journal for Pediatric and Congenital Heart Surgery, 2014)
Correlating postcardiotomy extracorporeal membrane oxygenation (ECMO) troponin I (TnI) levels and outcomes.Between January 2006 and August 2010, 34 patients needed postcardiotomy ECMO for low cardiac output. Bailout ECMO was required either after unsuccessful weaning from bypass (n = 17, 50%), postoperatively from prolonged hemodynamic failure (n = 8, 23.5%), or following resuscitation (n = 9, 26.5%). The TnI levels were measured following surgery or resuscitation during 10 days and compared between survivors (group I) and non-survivors (group II).Median support duration was seven days (range: 0-31). Surgery involving hypoplastic aortic arch repair (Norwood palliation; n = 7, 20.6%, or biventricular repair; n = 11, 32.4%) led to most ECMO runs. Successful weaning from ECMO and hospital survival were 76.5% and 50%, respectively. In group I, peak TnI levels were reached by 24 hours postoperatively, comparable to levels in group II (36 ± 34 vs 49 ± 38 ng/mL; P = .98). However, in group II, TnI levels formed a plateau by the second postoperative day, whereas group I showed a steep decline in TnI levels, suggesting myocardial recovery (P = .028). All patients (n = 4) who reached or maintained peak TnI levels at 48 hours died. On days 8, 9 and 10, TnI levels were significantly higher in group II (P = .024, .019, and .013, respectively).Postcardiotomy ECMO was most commonly required after aortic arch repair. In the absence of ongoing myocardial insult due to ECMO hardware issues, coronary insufficiency or residual lesions, plateau TnI levels at 48 hours may seem to indicate an unfavorable outcome due to irreversible myocardial damage.
EVALuna2:25107

Update on hemofiltration and hemoperfusion Update hämofiltration und hämoperfusion - Münch, Frank; Purbojo, Ariawan; Cesnjevar, Robert; Teske, Andreas (Kardiotechnik, 2019)
Extracorporeal circuits in CPB and ECMO/ ECLS represent a “necessary evil“ for ade-quately treating patients with a conforming diagnosis. The contact of blood to foreign surfaces, for instance the PVC tubing of CPB components, leads to pathophysiological reactions with corresponding and systemic negative effects for the patient. Foreign surface contact in the CPB circuit trigger, to a greater or lesser extent, an un-specific inflammatory response in the pa-tient. The release of highly active substances such as cytokines and complementary factors, intended for infection defense wit-wit-hout specific targets, can potentially cause damage to any organ. The resulting organ dysfunction is usually summarized under the term post-perfusion syndrome. The kidneys are very sensitive towards the pathophysiology of ECC. Even today postoperative acute kidney injury (AKI) remains a severe complication after cardiac surgery and is associated with high morbi-dity and mortality. It is indisputable that the altered hemodynamic of CPB has pathophysiological implications. Loss of pulsa-tile flow, inflammatory reactions, the pre-sence of free hemoglobin, hemolysis and vasoconstriction of the afferent glomerular arterioles with the resulting reduction of renal perfusion are part of the damaging me-chanism for both kidneys. These causes of AKI can be ameliorated with adequate cardiac output, normothermic perfusion and optimized fluid management [1]. As per-fusionists we often see the development of edema after ECC, especially in the lungs. Different modes of filtration and various filters are available to counteract interstitial edema. The use of ultrafiltration (UF), ze-ro-balance ultrafiltration (Z-BUF) and modified ultrafiltration (MUF) is associated with an improvement in pulmonary func-tion. The greatest benefits are seen in pediatric patients with the most striking mis-match between circuit size and body surface area [2]. It can be debated whether more in-ert materials in ECC circuits still require the use of hemofiltration or whether filters should be restricted in the ECC circuit after a risk-benefit analysis. From a techni-cal viewpoint the hemofilter is just additio-nal foreign surface area in the ECC circuit with consecutive pathophysiological reac-tions. A minimization of foreign surfaces as well as avoiding blood-air contact would reduce the number of damaging mediators released through blood-filter contact. In short, what is not released must not be eli-minated. However, our daily practice sees increasingly ill patients with multiple mor-bidities undergoing ECC or ECMO/ECLS, for whom we as perfusionists have to of-fer solutions to counteract ECC pathophysiology and disease-related dysfunctions. However, the elimination of immune-ac-tive mediators, thus diminishing their negative hout effects plays an important role. The use of adsorbers in ECC represents another promising, alternative for reducing or eli-minating damaging components dissolved in the blood plasma. In this article the me-chanisms of action as well as the applicabi-lity of hemofilters and adsorbents in daily use by perfusionists are presented and explained.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Acute kidney injury; Adsor-bers; Cardiopulmonary bypass; Hemofiltration; Ultrafiltration

Using medical plastics in perfusion Medizinische kunststoffe in der kardiotechnik - Münch, Frank; Göen, Thomas (Kardiotechnik, 2019)
Medical plastics are common technical industrial materials that are processed into medical products for medical applications under clean room conditions to ensu-re the strictest purity. The main advantages of plastics are their elasticity, ease of pro-cessing and low density. Disadvantages include lower mechanical strength and time-dependent degradation, in addition to the potential exuding of adjuvants in in-situ application and limited sterilizability due to lower thermal stability. The term “medical plastic” primarily denotes biocompatibility as a characteristic. A medical plastic should in particular be bioresistant and biocompa-tible, especially in direct and indirect contact with the human organism. Medical plastics are resistant to human biological material and other medical media. Chemi-cal resistance is also essential when plastics come into contact with disinfectants and acids, as in a medical setting. In addi-tion, medical plastics may have antimicro-bial properties. Additives to plastics allow their optimization in order to meet specific medical requirements. Polycarbonate, polypropylene, polyure-thane, polyvinyl chloride and silicone are key materials used in the application area of ext-racorporeal systems. Extracorporeal circulation components made of plastics include oxy-genators, heat exchangers, filters, reservoirs, connectors, cannulas, tubing, and more. There is no such thing as “the” perfect plastic, so compromises are often unavo-idable in material design. For example, highly biocompatible materials are usu-ally characterized by a low mechanical strength. The European Commission and the FDA recommend that medical materials used should have no relevant disadvantages for the patient. In extracorpore-al circulation tubing systems, for example, plasticizer migration into the blood can be significantly reduced by selecting suitab-le substitutes such as tri-(2-ethylhexyl)tri-mellitate (TEHTM, TOTM).Accordingly, PVC with the additive TOTM seems to have the least toxic risk on the organism. Like the tunica intima in the human organism, new concepts for composite materials and surface-modified materials promise impro-ved compatibility for plastics.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Additives; Extracorporeal circulati-on; Medical plastics; Toxicity

Verbesserte Qualität gelagerter Erythrozytenkonzentrate durch maschinelle Autotransfusion - Münch, Frank; Purbojo, Ariawan; Wenzel, F.; Kohl, M.; Dittrich, Sven; Rauh, Manfred; Zimmermann, Rüdiger; Kwapil, Nicola (Die Anaesthesiologie, 2022)
Background The transfusion of packed red blood cells (PRBC) is associated with various side effects, including storage damage to PRBCs. The cells change their structure, releasing potassium as well as lactate. Mechanical rinsing, available in many hospitals, is able to remove toxic substances and possibly minimizes the negative side effects of transfusion. Objective The primary aim of our study was to improve the quality of PRBCs before transfusion. The effects of different washing solutions on PRBC quality were analyzed. Material and methods This in vitro study compares 30 mechanically washed PRBCs. They were either processed with standard normal saline 0.9% (n = 15, N group) or a hemofiltration solution containing 4 mmol/l potassium (n = 15, HF group) by a mechanical rinsing device (Xtra, LivaNova, Munich, Germany). A subgroup analysis was performed based on the storage duration of the processed PRBCs (7, 14, 37 days). Samples were taken before washing (EKpra), immediately after washing (EKpost) and 10 h later (EKpost10h), after storage in the "wash medium" at room temperature. Concentrations of ATP (probability of survival in transfused erythrocytes), lactate, citrate and electrolytes (potassium, sodium, chloride, calcium) were tested. Results and conclusion Mechanical rinsing improves pretransfusion quality of PRBC. Washing with a hemofiltration solution results in a more physiological electrolyte composition. Even 10 h after mechanical rinsing with a hemofiltration solution, the quality of 37-day-old PRBC is comparable to young PRBC that have been stored for 7 days and have not been washed. Washing stored PRBC increases the ATP content, which subsequently leads to an increased probability of survival of red cells after transfusion.
CRIS-Team WoS Importer:2022-08-26